2019
DOI: 10.1371/journal.pone.0222510
|View full text |Cite
|
Sign up to set email alerts
|

Class III β-tubulin expression as a predictor of docetaxel-resistance in metastatic castration-resistant prostate cancer

Abstract: About half of the patients treated with docetaxel in the setting of metastatic castration-resistant prostate cancer (CRPC) are non-responders. Therefore, a marker of response would be beneficial for clinical decision-making. We evaluated class III β-tubulin (βIII-tubulin) expression as a predictor of resistance in this setting, which previously has been correlated with lack of response to taxanes in other cancers. Patients with CRPC were included if they were treated with at least 3 cycles of docetaxel between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Because every tumor is unique, a more individualized treatment plan with chemotherapy combined with an inhibitor to an altered pathway or an alternative chemotherapy may reverse resistance or could prevent it altogether. [193,338] MDR1 and other ABC transporter proteins Ovarian, Prostate In vitro [42,307,324,325] reviewed in [20] Expression of CYP2C8, 3A4, 3A5 Ovarian Human Specimens reviewed in [20] MAPs…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because every tumor is unique, a more individualized treatment plan with chemotherapy combined with an inhibitor to an altered pathway or an alternative chemotherapy may reverse resistance or could prevent it altogether. [193,338] MDR1 and other ABC transporter proteins Ovarian, Prostate In vitro [42,307,324,325] reviewed in [20] Expression of CYP2C8, 3A4, 3A5 Ovarian Human Specimens reviewed in [20] MAPs…”
Section: Discussionmentioning
confidence: 99%
“…The study by Ploussard et al even suggested that the increase in βIII-tubulin expression could be a result of taxane treatment after analyzing samples from patients with/without treatment as well as those sensitive/resistant to treatment [ 337 ]. More evidence has connected higher levels of βIII-tubulin in tissue samples from CRPC patients having at least three cycles of DTX with shorter overall survival and reduced responsiveness to taxane treatment [ 338 ]. βIII-tubulin levels are strongly associated with taxane resistance in CRPC and could act as a biomarker to predict patient response prior to treatment, enabling clinicians to prescribe alternatives and avoid resistance.…”
Section: Taxane Resistance In Prostate Cancermentioning
confidence: 99%
“…In a wide range of tumors and cancer cell lines, including small-cell lung carcinoma, NSCLC, ovarian, prostate, bladder, uterine, upper gastrointestinal, colon, pancreatic, LASCCHN, and gastric cancer, βIII upregulation is associated with the development of resistance to taxane-based chemotherapy and poor clinical outcome [ 121 , 200 , 202 , 203 , 204 , 205 , 206 , 207 , 208 , 210 , 211 , 212 , 213 , 215 , 223 , 224 , 225 , 226 , 227 , 228 , 229 , 230 , 231 , 232 , 233 ]. Moreover, an increased βIII level was also shown to be associated with EMT and cell motility of colon cancer cell lines [ 234 ].…”
Section: Factors Affecting Microtubule Dynamics In Cancer Cellsmentioning
confidence: 99%
“…Notably, despite of the small sample size, the extent of microtubule bundling was associated with DTX response [24] . [16][17][18][19]21,24] The increased expression of βIII-tubulin leads to DTX resistance. βIII-tubulin exhibits predictive value for DTX treatment 2.…”
Section: Tubulin Alterationsmentioning
confidence: 99%
“…Some studies have reported that overexpression of TUBB3 confers DTX resistance in PCa [ 17 , 18 ] . The status of TUBB3 expression has a predictive value for OS in CRPC patients treated with DTX [ 17 , 19 ] . MAPT, which encodes the microtubule-associated protein tau, works in tubulin assembly and microtubule stabilization [ 20 ] .…”
Section: Mechanisms Of Resistance To Docetaxel In Prostate Cancermentioning
confidence: 99%